Efficiency of Sensory Substitution Devices Alone and in Combination With Self-Motion for Spatial Navigation in Sighted and Visually Impaired - Jicol, Crescent; Lloyd-Esenkaya, Tayfun; Proulx, Michael J.; Lange-Smith, Simon; Scheller, Meike; O'Neill, Eamonn; Petrini, Karin (Frontiers in Psychology, 2020)
Human adults can optimally combine vision with self-motion to facilitate navigation. In the absence of visual input (e.g. dark environments and visual impairments), sensory substitution devices (SSD), such as The vOICe or BrainPort which translate visual information into auditory or tactile information, could be used to increase navigation precision when integrated together or with self-motion. In Experiment 1, we compared and assessed together The vOICe and BrainPort in aerial maps task performed by a group of sighted participants. In Experiment 2, we examined whether sighted individuals and a group of visually impaired individuals could benefit from using The vOICe, with and without self-motion, to accurately navigate a three-dimensional environment. In both studies, 3D motion tracking data were used to determine the level of precision with which participants performed two different tasks (an egocentric and allocentric task) and three different conditions (two unisensory conditions and one multisensory condition). In Experiment 1 we found no benefit of using the devices together. In Experiment 2, the sighted performance during The vOICe was almost as good as that for self-motion despite a short training period, although we found no benefit (reduction in variability) of using The vOICe and self-motion in combination compared to the two in isolation. In contrast, the group of visually impaired participants did benefit from combining The vOICe and self-motion despite the low number of trials. Finally, while both groups became more accurate in their use of The vOICe with increased trials, only the visually impaired group showed an increased level of accuracy in the combined condition. Our findings highlight how exploiting non-visual multisensory integration to develop new assistive technologies could be key to help blind and visually impaired persons especially due to their difficulty in attaining allocentric information.